Online textbook payment for Koperasi UiTM using standing order account / Ashamahani Ahmad - Ahmad, Ashamahani (2006)
Online bookstore has become one of the effective ways to market various kinds of books. There are many types of electronic payment methods available to be used in online shopping environment. Standing Order Account is used as the payment method in developing Online Textbook Payment System (OTPS) for Koperasi UiTM. Standing Order Account enables the account holder to make a fix purchase of something at regular intervals. Currently, there is no system in Koperasi UiTM that enables the students to purchase textbook online. Koperasi UiTM handles the textbook purchasing activity manually and only accepts cash for the textbook purchased. The development of OTPS allows the students to purchased textbook online without using cash at all since the price of the textbook purchased will be deducted from the account itself The purposes of this research are to identify the requirements and data needed in developing OTPS, to analyze the requirements captured and data gathered to design the OTPS and to develop Online Textbook Payment for Koperasi UiTM using Standing Order Account as the payment method. Interview, questionnaire and websites observation of several international and local campus bookstores are among the methods used in conducting this research. The release of OTPS introduces the alternative way in online payment activities.